Outcomes and prognostic factors of alternative treatment regimens for angioimmunoblastic T-cell lymphoma: a retrospective analysis - Yan, Jiaqin; Wang, Jiebing; Zhang, Junhui; Zhang, Xudong; Zhang, Lei; Zhu, Zunmin; Zhang, Mingzhi (Frontiers in Oncology, 2025)
BackgroundAngioimmunoblastic T-cell lymphoma (AITL), representing the second most prevalent subtype of peripheral T-cell lymphoma, currently lacks standardized frontline therapeutic strategies.MethodsIn this study, we evaluated the survival outcomes and prognostic factors in 154 patients with AITL treated with one of four regimens: CHOP (cyclophosphamide, vincristine, epirubicin, prednisone), CHOPE (CHOP + etoposide), CPET (chidamide, prednisone, etoposide, thalidomide), or GDPT (gemcitabine, cisplatin, dexamethasone, thalidomide). Among them, 144 patients had complete survival follow-up data. Survival differences across groups were analyzed using the log-rank test, while variations in clinical parameters were assessed via chi-square tests and one-way ANOVA. Univariate and multivariate Cox regression analyses were conducted to identify factors associated with progression-free survival (PFS) and overall survival (OS).ResultsThe 5-year OS and PFS rates for the entire cohort were 36.6% (95% CI: 0.275–0.488) and 32.2% (95% CI: 0.233–0.451), respectively. Patients who were younger (<60 or <70 years), had Ann Arbor stage I/II disease, or exhibited lower Eastern Cooperative Oncology Group (ECOG) performance status scores demonstrated significantly improved OS and PFS following treatment. Notably, among patients with ECOG <2, those treated with the CPET regimen achieved longer PFS and OS compared to those receiving CHOP or CHOPE. In contrast, for patients with ECOG ≥2, no significant survival differences were observed across treatment regimens. Both univariate and multivariate analyses identified ECOG performance status as an independent prognostic factor for survival outcomes.ConclusionFor patients with a low ECOG performance status, the CPET regimen may offer promising survival outcomes.